PEMBERDAYAAN PEREMPUAN DALAM PELESTARIAN ORANGUTAN DI DUSUN TEMBAK, DESA GURUNG MALI,KABUPATEN SINTANG, KALIMANTAN BARAT - Faraz Sumaya (Jurnal Penelitian Sosial dan Ekonomi Kehutanan, 2021)
Tembak Hamlet is the first orangutan school area built by the Sintang Orangutan Center (SOC). One of the programs is empowering women to make orangutan dolls. Part of the proceeds from the sale will be donated to the operational activities of the orangutan school. The SOC is aware that socio-cultural and economic aspects significantly influence the successful implementation of the orangutan school program. This study was analyzed using the empowerment ladder concept and Symbolic Interactionism Theory. This study aimed to analyze the empowerment of women in Tembak Hamlet and its socio-economic impacts. The research uses a qualitative method. Data were collected through observation, interviews, and documentation. Respondents in this research consist of 6 purposively determined people. This analysis is expected to be a reference material for orangutan conservation organizations in other places to pay more attention to the socio-cultural and economic aspects of the community. The results showed that the process in the empowerment stage formed the meaning of orangutan conservation in the women of the orangutan doll-making group. Women use orangutan dolls as a symbol of women's contribution to protecting customary forests and orangutans